Achieving the First Best in Sequencing Problems - Manipushpak Mitra (University of Bonn, Bonn Graduate School of Economics (BGSE), 2000)
In a sequencing problem with linear time cost, Suijs (1996) proved that it is possible to achieve first best. By first best we mean that one can find mechanisms that satisfy efficiency of decision, dominant strategy incentive compatibility and budget balancedness. In this paper we show that among a more general and natural class of sequencing problems, sequencing problems with linear cost is the only class for which first best can be achieved.
Keywords: C72; C78; D82; 330; Sequencing problems; Dominant strategy incentive compatibility; Efficiency; Budget balancedness